Stefano D. T orre, Massimiliano Bocciarelli, Laura Daglio, Raffaella Neri (Eds) Buildings for Education. A Multidisciplinary Overview of The Design of School Buildings, Springer, Cham 2020, pp. 327 - Adamczewski, Jakub (Studia Edukacyjne, 2021)
Review. Stefano D. T orre, Massimiliano Bocciarelli, Laura Daglio, Raffaella Neri (Eds) Buildings for Education. A Multidisciplinary Overview of The Design of School Buildings, Springer, Cham 2020, pp. 327.